Maastricht II: Are real convergence criteria needed? - Christian Schmidt; Thomas Straubhaar (Intereconomics, 1995)
In the run-up to the Intergovernmental Conference of the Member States of the EU in 1996, criticism of the convergence criteria laid down in the Maastricht Treaty selection and the scope left for interpretation is becoming ever vociferous. Will the shortcomings be rectified if, as demanded by the British Government in particular, the monetary and fiscal convergence criteria are complemented by real economic criteria?
Keywords: 330; EU